Two different anticonvulsant actions of tiagabine in developing rats - Haugvicová, R; Skutová, M; Kubová, H; Suchomelová, L; Mares, P (Epilepsia, 2000)
PURPOSE: Our goal was to study the anticonvulsant action of tiagabine (TGB) at different levels of brain maturation in rats. METHODS: Wistar rats in five age groups (7, 12, 18, 25, and 90 days old) were injected intraperitoneally with TGB at doses of 0.5-32 mg/kg. Thirty minutes later, motor seizures were induced by the subcutaneous adminstration of pentylenetetrazol (PTZ) in a dose of 100 mg/kg for all of the groups except the 18-day-old rat pups, which received a 90-mg/kg dose. The incidence and latency of two types of motor seizures, minimal clonic and generalized tonic-clonic seizures (GTCSs), were evaluated, and the seizure severity was scored. The time profile of TGB action at the 8-mg/kg dose was studied in the 12-and 25-day-old rats. RESULTS: Minimal clonic seizures were reliably induced in rats 18 days old or older, and the seizures were suppressed by TGB in all of these age groups. Although TGB was very effective against this type of seizure in the 18-day-old rats, the efficacy of the drug decreased with the age of the animal. GTCSs were suppressed by TGB in the adult and 25-day-old rats, and a U-shaped dose-response curve was outlined in these two groups. The 18-and 12-day-old rat pups exhibited a selective suppression of the tonic phase of GTCSs. A mixture of these two effects was observed in the youngest group. TGB demonstrated a markedly longer action in the 12-day-old rats than in the 25-day-old rats. CONCLUSIONS: TGB exhibits anticonvulsant action against both minimal seizures and GTCSs. Ontogenetic development of these two actions is markedly different.
Keywords: Dose-Response Relationship, Drug; záchvaty; Epilepsy, Tonic-Clonic; vztah mezi dávkou a účinkem léčiva; Pentylenetetrazole; Rats; Animals, Newborn; epilepsie tonicko-klonická; Epilepsy, Generalized; Disease Models, Animal; antikonvulziva; Rats, Wistar; Tiagabine; mozek; Seizures; novorozená zvířata; krysa rodu Rattus; věkové faktory; Brain; modely nemocí na zvířatech; tiagabin; zvířata; Anticonvulsants; Age Factors; Nipecotic Acids; kyseliny nipekotinové; potkani Wistar; pentylentetrazol; epilepsie generalizovaná; Animals